2019
DOI: 10.1093/jac/dkz516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phthalazinone phosphodiesterase inhibitors with improved activity and selectivity against Trypanosoma cruzi

Abstract: Background Chagas’ disease, caused by the protozoan parasite Trypanosoma cruzi, needs urgent alternative therapeutic options as the treatments currently available display severe limitations, mainly related to efficacy and toxicity. Objectives As phosphodiesterases (PDEs) have been claimed as novel targets against T. cruzi, our aim was to evaluate the biological aspects of 12 new phthalazinone PDE inhibitors against different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…These observations are suggestive of osmotic stress and may be related to increased levels of cAMP. In this context, we investigated the possibility of a PDE target for NPD-227 and observed that it induced a significant increase in the cellular cAMP concentration, confirming the targeting of at least one PDE parasite isoform, consistent with reports on other PDE inhibitor chemotypes (25,26).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These observations are suggestive of osmotic stress and may be related to increased levels of cAMP. In this context, we investigated the possibility of a PDE target for NPD-227 and observed that it induced a significant increase in the cellular cAMP concentration, confirming the targeting of at least one PDE parasite isoform, consistent with reports on other PDE inhibitor chemotypes (25,26).…”
Section: Discussionsupporting
confidence: 85%
“…The rounding of parasites induced by NPD-227 suggests an impact on the osmoregulation system, already described as an outcome of PDEC inhibition in T. cruzi (9). Indeed, we have previously shown that exposure to other classes of PDE inhibitors, specifically imidazoles (25) and phthalazinones (26), causes profound ultrastructural damage in the Golgi, flagellar pocket, and plasma membrane of T. cruzi. These observations are suggestive of osmotic stress and may be related to increased levels of cAMP.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The essentiality of the cAMP signaling pathways, including PKA, prompted us to extend our work on cAMP phosphodiesterases of protozoan parasites [ 28 32 ] to S . mansoni , anticipating that, as in human-infective protozoa, inhibition of PDEs leads to a fatal increase and imbalance in cellular cAMP levels.…”
Section: Introductionmentioning
confidence: 99%